Chemical engineering of a lipid nano-scaffold for the solubility enhancement of an antihyperlipidaemic drug, simvastatin; preparation, optimization, physicochemical characterization and pharmacodynamic study. (17th November 2018) - Alam, Meraj; Ahmed, Shakeeb; , Nikita; Moon, Goldie; Aqil, Mohd.; Sultana, Yasmin
Abstract: This project was designed to extract anti-hyperlipidaemic activity of simvastatin for the longer duration of time and the solubility enhancement of this BCS class II drug was also sought by preparing nanostructured lipid carrier (NLC). The method for NLC preparation involved melt-emulsification followed by ultrasonication. The developed formulation was optimized by 3-level, 3-factor Box–Behnken design. The independent variables were % lipid mixture, % surfactant and sonication time (minutes). The responses selected were particle size, PDI and entrapment efficiency. The optimized formulation had particle size 114.62 ± 5.65, PDI 0.210 ± 0.034 and entrapment efficiency 85.20 ± 7.98%. The optimized formulation was further characterized by TEM and SEM. Spherical shape and nano size distribution of the optimized formulation were confirmed by SEM and TEM, respectively. The DSC of optimized formulation hints for the loss of crystalline nature of drug whereas the FT-IR spectra reveal that there is no interaction between drug and excipients when incorporated in NLC. The drug release from the NLC was biphasic (burst release was followed by sustained release). The kinetic of drug release followed Fickian diffusion with Korsmeyer–Peppas model. When the antihyperlipidaemic activity of SMV-NLC was compared with SMV-suspension, it was found that SMV-NLC significantly decreased the total cholesterol and triglyceride level by 2.77 and threefolds, respectively. Graphical Abstract: